Az élethosszig tartó tanulás mérésének kihívásai és a jelenség kutatásának jellegzetességei a nemzetközi kutatásokban - Flick-Takács, Nikolett (Magyar Pedagógia, 2019)
Although the first study on lifelong learning was published in the 1960s, reviewing the science-metric database of Scopus shows that this concept began to gain popularity in science only from the 2000s (Wolfe, 1964). The reasons for this are probably the reforms at international levels of educational policy, which have declared the need to promote lifelong learning among OECD countries. (OECD, 2007). Although the concept has gone through some changes, and its interpretation has widened in regulatory documents since its inception, pedagogical practice and scientific research haven’t caught up with these changes yet (Magyarország Kormánya, 2015; UNESCO, 2016). Taking a closer look at the scientific works in the Scopus database reveals that by the end of 2019, there are a total of 1,791 papers presenting research or theoretical work on lifelong learning. However, only a small proportion of these – 143 documents in total – goes beyond „lifelong education” and uses the broader concept of „lifelong learning” which also includes early phase development (Scopus, 2019). Most of these studies work with samples of teachers (Uzunboylu & Hürsen, 2011; Klug et. al., 2014; Hursen, 2014; Hursen, 2016; Tezer & Aynas, 2018; Selcuk et. al., 2018) or undergraduate students (Coşkun & Demirel, 2010; Kirby et. al., 2010; Feng & HA, 2016). Given that the early stages of lifelong learning have not yet been investigated thoroughly, in my study, I would like to point out some of the factors that may influence the research of the field, such as the characteristics of the definition of the concept and the researchability of the phenomenon. Challenges in defining the concept include the heterogeneity of different definitions in science and the differences between interpretations of education policy and education practice. Among the challenges of researchability, there are problems arising from the complexity of the phenomenon, the limitations of research with interviews (e.g.: action-research studies that would require further research), (Klug et al., 2014; Hursen, 2014), as well as questionnaire research, which does not fully cover the phenomenon with closed questions and Likert scales, that’s why most of the published studies working with questionnaires use so many items (Crick et. al., 2002; Coskun & Demirel, 2010; Uzunbuylu & Hürsen, 2010; Günüc et. al., 2014; Selcuk et. al. 2018; Lawthong & Kanjanawasee, 2018). At the same time, due to the lack of a universal theoretical framework, factor structures are often interpreted in an indistinctly structured framework (Günüc et al., 2014; Kirby et al., 2010). All in all, we can see that although the topic of lifelong learning is very popular among researchers, according to the Scopus database, research starting out from a wider interpretation of the concept (including the early stages as well) is still the task of the future.